The Ideological Development of ?Power? in Early American Pentecostalism An Historical, Theological, and Sociological Study. - Althouse, Peter (Lewiston : Edwin Mellen Press, 2010)
This is study on the central concept of ?power? in early Pentecostalism which examines the historical development of the language of power in Wesleyan Holiness and American Revivalism and how it fueled early Pentecostal experiences of the Spirit, spiritual practices and theological descriptions.
Description based upon print version of record.
Keywords: Pentecostalism -- United States -- History -- 20th century; Power (Christian theology) -- History of doctrines -- 20th century; United States -- Church history -- 20th century; Pentecostalism -- United States -- History -- 20th century; Power (Christian theology) -- History of doctrines -- 20th century; United States -- Church history -- 20th century; RELIGION / Christianity / History; Electronic books